2008
DOI: 10.1016/j.addbeh.2008.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Relapse to smoking after 1 year of abstinence: A meta-analysis

Abstract: Most clinical trials use 6 mo or 1 yr follow-ups as proxies for life-time smoking cessation. Retrospective studies have estimated 2-15% of smokers relapse each year after the first 1 year of abstinence, but these have methodological problems such as memory bias. We searched for prospective studies of adult quitters that reported the number of participants abstinent at 1 yr followup and who remained abstinent at ≥ 2 year follow-ups. We included studies that reported the percent who remained lapse-free, did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
122
3
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(130 citation statements)
references
References 22 publications
3
122
3
2
Order By: Relevance
“…These results extend earlier findings indicating that URB597 blocks the acquisition of nicotine selfadministration in rats (Scherma et al, 2008), and represents the first demonstration that FAAH inhibitors can also decrease nicotine self-administration that has already been acquired and maintained at a stable rate in animals. In addition, both FAAH inhibitors had robust effects in the reinstatement model of relapse to nicotine seeking in abstinent monkeys, blocking reinstatement triggered by reexposure to either nicotine itself or to nicotine-associated environmental cues; these findings suggest that FAAH blockade might prevent craving and relapse to smoking, the latter of which is widely considered the main obstacle to smoking cessation (Herd et al, 2009;Hughes et al, 2008). These findings in non-human primates provide the best preclinical evidence available that FAAH inhibitors could be beneficial as smoking-cessation medications in humans.…”
Section: Discussionmentioning
confidence: 92%
“…These results extend earlier findings indicating that URB597 blocks the acquisition of nicotine selfadministration in rats (Scherma et al, 2008), and represents the first demonstration that FAAH inhibitors can also decrease nicotine self-administration that has already been acquired and maintained at a stable rate in animals. In addition, both FAAH inhibitors had robust effects in the reinstatement model of relapse to nicotine seeking in abstinent monkeys, blocking reinstatement triggered by reexposure to either nicotine itself or to nicotine-associated environmental cues; these findings suggest that FAAH blockade might prevent craving and relapse to smoking, the latter of which is widely considered the main obstacle to smoking cessation (Herd et al, 2009;Hughes et al, 2008). These findings in non-human primates provide the best preclinical evidence available that FAAH inhibitors could be beneficial as smoking-cessation medications in humans.…”
Section: Discussionmentioning
confidence: 92%
“…While the majority of cigarette smokers endorse the desire to quit, reported abstinence rates after twelve months are in the modest region of 5-17% (Hughes et al, 2008), with the vast majority relapsing to smoking within a week of cessation (Zhu et al, 2012). Executive functioning has been proposed to play a significant role in preventing relapse (Buhringer et al, 2008;Garavan et al, 2013), and indeed, research has reported that long-term abstinent ex-smokers demonstrate hyperactivity in lateral and medial prefrontal regions that sub-serve inhibitory control functioning (Kroenke et al, 2015;Nestor et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Barriers in recording smoking status are well documented, such as limited time in clinic, providers lacking training, and perception of low quitting success rates [15] . Numerous studies support that increased training and education of health care providers results in greater monitoring of smoking status and implementation of smoking cessation interventions [15][16][17][18] . It stands to reason therefore that registration of smoking status has the potential to follow similar trends in Greenland as seen elsewhere.…”
Section: Discussionmentioning
confidence: 99%
“…This is further reflected by the fact that 3.5% of the patient study population were noted to start smoking during the study period but in fact almost exclusively represented relapsed smokers. Estimated 1 year relapse rates are typically 10% [16] . Therefore we suspect rates of prolonged abstinence to be lower than quitting rates noted in our point-prevalence study.…”
Section: Discussionmentioning
confidence: 99%